INTRODUCTION OF DIGITAL ENTREPRENEURSHIP IN INTERNATIONAL HIGH SCHOOLS INDONESIA KUALA LUMPUR (SIKL) - Kencana, Putri Nilam; Sunarto, Ading; Wahidah, Nur Rachma (International Journal of Engagement and Empowerment (IJE2), 2024)
Education is essential in increasing human resources; several small Indonesian communities in Malaysia, due to administrative problems which cause these communities to need access to education. Entrepreneurship is an important thing that needs to be introduced from an early age so that an entrepreneurial spirit can be formed in a person. The purpose of this service is to provide an introduction to entrepreneurship at International High Schools (Sekolah et al.) Malaysia. The activity offered in this activity is to provide an introduction to entrepreneurship with improved technology with student-based learning lectures with students at international high schools. Activities will be carried out in January with the International Senior High School Leadership (SIKL Malaysia). The output target of this service is (1). Sinta 5 indexed scientific articles, National Seminar Dissemination, Mass media publications, and introduction to entrepreneurship in high schools (SIKL-Malaysia)